Factors Associated With Family Caregivers’ Knowledge and Attitudes Toward Home-Based Geriatric Care in Primary Healthcare: A Cross-Sectional Study - Savitri Gemini; Nur Indrawati Lipoeto; Rizanda Machmud; Arina Widya Murni (Majalah Kesehatan Indonesia, 2026)
Family caregivers play a central role in home-based geriatric care, especially in settings where institutional long-term care remains limited. However, caregiver capacity may vary according to socio-demographic, relational, and service-related factors. This study aimed to identify factors associated with family caregivers’ knowledge and attitudes toward home-based geriatric care in a primary healthcare context. A quantitative analytic study with a cross-sectional design was conducted from September to December 2025 in two Puskesmas working areas in Batam City, Indonesia. A total of 326 family caregivers were recruited using proportional sampling. Data were collected through structured questionnaires and analyzed using univariate analysis, Chi-square tests, and multivariate logistic regression. Most caregivers had low knowledge (86.5%) and negative attitudes (61.0%) despite reporting high communication patterns and positive perceptions of healthcare facility quality. Bivariate analysis showed that economic status, caregiving duration, communication pattern, and perceived quality of healthcare facilities were significantly associated with knowledge, whereas economic status, communication pattern, and perceived quality of healthcare facilities were associated with attitudes. In the multivariate model, only caregiving duration (AOR = 15.790; p < 0.001) and communication pattern (AOR = 0.157; p = 0.013) remained independently associated with caregiver knowledge. No independent predictors were identified for attitudes. These findings indicate that caregiver knowledge was more strongly associated with experiential and relational factors, particularly caregiving duration and family communication. Structured, family-centered, and nurse-led interventions in primary healthcare may help strengthen caregiver preparedness in home-based geriatric care. Abstrak: Caregiver keluarga memainkan peran sentral dalam perawatan geriatri berbasis rumah, terutama di lingkungan yang layanan perawatan jangka panjang institusionalnya masih terbatas. Namun, kapasitas caregiver dapat bervariasi menurut faktor sosiodemografis, relasional, dan faktor terkait layanan. Penelitian ini bertujuan untuk mengidentifikasi faktor-faktor yang berhubungan dengan pengetahuan dan sikap caregiver keluarga terhadap perawatan geriatri berbasis rumah dalam konteks pelayanan kesehatan primer. Penelitian kuantitatif analitik dengan desain potong lintang dilakukan dari September hingga Desember 2025 di dua wilayah kerja Puskesmas di Kota Batam, Indonesia. Sebanyak 326 caregiver keluarga direkrut menggunakan proportional sampling. Data dikumpulkan melalui kuesioner terstruktur dan dianalisis menggunakan analisis univariat, uji Chi-square, dan regresi logistik multivariat. Sebagian besar caregiver memiliki pengetahuan rendah (86,5%) dan sikap negatif (61,0%) meskipun melaporkan pola komunikasi yang tinggi dan persepsi positif terhadap kualitas fasilitas pelayanan kesehatan. Analisis bivariat menunjukkan bahwa status ekonomi, lama merawat, pola komunikasi, dan persepsi terhadap kualitas fasilitas pelayanan kesehatan berhubungan secara signifikan dengan pengetahuan, sedangkan status ekonomi, pola komunikasi, dan persepsi terhadap kualitas fasilitas pelayanan kesehatan berhubungan dengan sikap. Pada model multivariat, hanya lama merawat (AOR = 15,790; p < 0,001) dan pola komunikasi (AOR = 0,157; p = 0,013) yang tetap berhubungan secara independen dengan pengetahuan caregiver. Tidak ditemukan prediktor independen untuk sikap. Temuan ini menunjukkan bahwa pengetahuan caregiver lebih kuat berhubungan dengan faktor pengalaman dan relasional, khususnya lama merawat dan komunikasi keluarga. Intervensi yang terstruktur, berpusat pada keluarga, dan dipimpin oleh perawat di pelayanan kesehatan primer berpotensi membantu memperkuat kesiapan caregiver dalam perawatan geriatri berbasis rumah.